Apa l’Etrusco sbarca a Roma e passa il testimone ad Ati. Un cortometraggio tridimensionale per raccontare il santuario di Portonaccio a Veio - Russo, Alfonsina; De Lucia, Maria Anna; Cosentino, Rita; Guidazzoli, Antonella; Imboden, Silvano; De Luca, Daniele; Liguori, Maria Chiara; Verri, Luigi; Bellavia, Giovanni (Archeomatica, 2015)
Computer graphics movies are a favourite media for edutainment. The 3D stereoscopic short movie "Ati at the discovery of Veii” is an interesting example of philologically accurate reconstructions coupled with a communication aimed at a wide audience. Developed by Cineca for a joint project involving the National Etruscan Museum of Villa Giulia and Genus Bononiae – Museum of the History of Bologna, the movie is grounded on the software Blender and a strong open source commitment.